Assessment of otolith function using vestibular evoked myogenic potential in women during pregnancy - Bhavana,G. (2022)
Abstract Introduction: More than 50% of pregnant women experience dizziness frequently in the first two gestational trimesters. During pregnancy, the changes in the metabolism of hormones are responsible for the ovarian cycle resulting in either peripheral or central vestibular alterations. The need for the study is to focus on the effect of changes during pregnancy on the vestibular evoked myogenic potential, an electrophysiological measure that investigates functions of the otolith structures. Objectives: The aim is to investigate the vestibular evoked myogenic potential responses during the first trimester of pregnancy. Methods: A total of 17 pregnant women and 17 non-pregnant women with age matched took part in this study. The cervical vestibular evoked myogenic potential were recorded from the ipsilateral sternocleridomastoid muscle and the ocular vestibular evoked myogenic potential were recorded from contralateral extraocular muscle in both groups. Results: Peak to peak amplitude of cervical vestibular evoked myogenic potential and ocular vestibular evoked myogenic potential was found to be significantly reduced in the responses obtained from first-trimester pregnant women when compared to that of non-pregnant women. Conclusions: Vestibular evoked myogenic potential tests exhibits a clinically significant reduced peak to peak amplitude in the first trimester of pregnancy, which indicates dysfunction in the otolith reflex pathway.